Determinants of Cooking Fuel Choices in Urban Nigeria - AKOMOLAFE, John Kehinde; OGUNLEYE, E.O. Esthere (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017DO - 10.14505//jemt.v8.1(17).17, 2017)
Despite the abundant deposit of gas resources in Nigeria, a large proportion of the country’s population still depend on traditional fuels such as firewood for cooking. This study investigates the determinants of households’ fuel choice in urban Nigeria. This study made use of primary data which were collected through administration of questionnaires in twelve states spread across six geopolitical zones in Nigeria. The cooking fuels examined are firewood, kerosene, LPG, and electricity. Multinomial logit model was used to estimate the determinants of fuel choices. The results showed that income, age of the wife, education level of the wife, and household size were important factors that determine cooking fuel choices across the country. The paper concludes that efforts should be aimed at making clean cooking fuels especially LPG affordable and available for urban households.